2022
DOI: 10.1155/2022/6755407
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-19 Aggravates Pulmonary Fibrosis via Activating Fibroblast through TGF-β/Smad Pathway

Abstract: Background. Idiopathic pulmonary fibrosis (IPF) is a progressive and fatal interstitial pneumonia disease with no cure. Communication between injured cells is triggered and maintained by a complicated network of cytokines and their receptors. IL-19 is supported by increasing evidences for a deleterious role in respiratory diseases. However, its potential role in lung fibrosis has never been explored. Methods. Bioinformatic, immunohistochemistry and western blot analysis were used to assess the expression of IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
(61 reference statements)
0
6
0
Order By: Relevance
“…Pathologically, IP is a common representative of idiopathic pulmonary fibrosis, and the final feature of IP is pulmonary interstitial fibrosis. 20 Therefore, referring to the previous research methods, 21 the inhibitory effect of drugs on TGF-β1-induced HELF cell fibrosis was explored through HELF cells, which could reflect the mechanism of drugs in IP from a specific perspective. Firstly, we analyzed the effect of changes in luteolin and diosgenin concentration on cell viability by CCK-8 method.…”
Section: Resultsmentioning
confidence: 99%
“…Pathologically, IP is a common representative of idiopathic pulmonary fibrosis, and the final feature of IP is pulmonary interstitial fibrosis. 20 Therefore, referring to the previous research methods, 21 the inhibitory effect of drugs on TGF-β1-induced HELF cell fibrosis was explored through HELF cells, which could reflect the mechanism of drugs in IP from a specific perspective. Firstly, we analyzed the effect of changes in luteolin and diosgenin concentration on cell viability by CCK-8 method.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed IL-19 is a member of the IL-10 family and is produced primarily by macrophages [16]. IL-19 is expressed in many organs, such as skin [16], lung [34] and intestine [16].…”
Section: Discussionmentioning
confidence: 98%
“…IL-19 is a member of the IL-10 family and is produced primarily by macrophages [ 16 ]. It is expressed in many organs, such as the skin [ 16 ], lungs [ 34 ], and intestines [ 16 ]. IL-19 expression in the pancreas was confirmed in exocrine glandular cells and mixed immune cells [ 35 ], according to single cell RNA-seq data from the Human Protein Atlas (HPA).…”
Section: Discussionmentioning
confidence: 99%
“… 84 It is evident that Interleukin‐19 (IL‐19) has great anti‐inflammatory properties, especially in vascular diseases, 85 yet, this function is not evident in the case of PF. Combination of wet lab and dry lab techniques has led to this understanding that IL‐19 is elevated in fibrotic lung ( 86 ). It was demonstrated that this cytokine has adverse effects on idiopathic pulmonary fibrosis (IPF) both in vitro and in vivo ( 86 ).…”
Section: Antioxidants As a Modulator Of Tgf ‐β/ ...mentioning
confidence: 99%
“…Combination of wet lab and dry lab techniques has led to this understanding that IL‐19 is elevated in fibrotic lung ( 86 ). It was demonstrated that this cytokine has adverse effects on idiopathic pulmonary fibrosis (IPF) both in vitro and in vivo ( 86 ). Interestingly, all of the mentioned effects are directly reversed by LY2109761, which inhibits TGF‐β/ SMAD signalling pathway ( 86 ).…”
Section: Antioxidants As a Modulator Of Tgf ‐β/ ...mentioning
confidence: 99%